Test of articulation in bengali - Arun Banik (Journal of All India Institute of Speech and Hearing, 1970)
Studies in Articulation test in Indian Languages are not many. Uptill now few articulation tests are developed in Indian languages such as Ram Mohan Babu et. al(1972) in Kannada, Usha (1986) in Tamil and Padmaja (1988) in Telegu. But such articulation tests cannot be used with people who speak other languages in India. To overcome all these problem there is a dire necessity to develop the standardized articulation tests in all the Indian languages.